Teachers` level of support in the use of teaching and learning resources of learners who are physically challenged in regular primary Schools in Kisumu West Sub County, Kenya. - Obara , Dorine Adhiambo; Were, Charles Michael (Advances in Social Sciences Research Journal, 2020)
The Government of Kenya made inclusive education a policy requirement in the provision of education to all children. Research has shown that the support given by teachers plays a very important role in curriculum implementation that ensures success in a child`s career. Education Assessment records in Kisumu county indicate that between the year 2012 and 2016, 846 learners who are physically challenged had been assessed and placed in regular schools in Kisumu West, Kisumu Central and Kisumu East sub-counties, out of which 246 had dropped out of school. However, Learners who are physical challenged often drop out of school more as compared to their regular counterparts particularly in Kisumu West Sub-County. The number of learners who are physically challenged enrolled in regular primary schools has been decreasing due to dropouts despite the fact that officers in Kisumu EARC conducted sensitization programs and workshops yearly for teachers and stakeholders in education. This decrease is confirmed at 138 (31.9%), which is higher as compared to the dropout of neighboring sub-counties namely: Kisumu East 31 (21.8%) and Kisumu Central 77(28.4%). Reason for this high dropout has not been established. The purpose of this study was therefore to establish teachers’ level of support in the use of teaching and learning resources of learners who are physically challenged in regular primary schools in Kisumu West Sub-County and objective of this study therefore was to establish teachers’ level of support in the use of teaching and learning resources of learners who are physically challenged. A conceptual framework was used to show the interaction of dependent and independent variables. The study adopted descriptive survey research design. Target population of the study consisted of 15 head teachers, 30 teachers, 6 EARC coordinators and 90 learners who are physically challenged. Saturated sampling technique was used to select 13 head teachers and 4 EARC coordinators, while purposive sampling was used to select 27 teachers and 81 learners who are physically challenged. Data was collected using questionnaires, interview schedules and observation checklist. Face and content validity of instruments was established through expert judgment and revision. Reliability of instruments was established through test-retest method on 10% of study population using Pearson’s product correlation. Reliability coefficient for head teachers questionnaire was 0.8, teachers’ questionnaires was 0.9; Learners who are physically challenged questionnaires was 0.7. This was above the accepted value of 0.7. Correlation coefficient analysis was used to establish teachers’ level of support in the use of teaching and learning resources f learners who are physically challenged. Quantitative data was analyzed using frequency counts, percentages and mean. Qualitative data from interview and observation schedules were collected, organized and categorized into themes and sub-themes, which were reported. Findings of the study indicated that most regular primary schools did not have adequate adapted teaching and learning resources required for learners who are physically challenged. The study recommended that Ministry of Education should ensure adequate supply of adapted teaching and learning resources, Findings of this study would be useful to teachers, EARC coordinators, and Ministry of Education.